Low pressure plasma-sprayed Al(2)O(3) and Al(2)O(3)/SiC nanocomposite coatings from different feedstock powders - Jiansirisomboon, S; MacKenzie, K; Roberts, S; Grant, P (2003)
This paper describes a preliminary investigation of a nanocomposite ceramic coating system, based on Al2O3/SiC. Feedstock Al2O3/SiC nanocomposite powder has been manufactured using sol-gel and conventional freeze-drying processing techniques and then low pressure plasma sprayed onto stainless steel substrates using a CoNiCrAlY bond coat. Coatings of a commercial Al2O3 powder have also been manufactured as a reference for phase transformations and microstructure. The different powder morphology and size distribution resulting from the different processing techniques and their effect on coating microstructure has been investigated. Phase analysis of the feedstock powders and of the as-sprayed coatings by X-ray diffractometry (XRD) and nuclear magnetic resonance (NMR) showed that the nano-scale SiC particles were retained in the composite coatings and that equilibrium α-Al2O3 transformed to metastable γ- and δ-Al2O3 phases during plasma spraying. Other minority phases in the sol-gel Al2O3/SiC nanocomposite powder such as silica and aluminosilicate were removed by the plasma-spraying process. Microstructure characterisation by scanning electron microscopy (SEM) of the as-sprayed surface, polished cross-section, and fracture surface of the coatings showed evidence of partially molten and unmolten particles incorporated into the predominantly lamella microstructure of the coating. The extent of feedstock particle melting and consequently the character of the coating microstructure were different in each coating because of the effects of particle morphology and particle size distribution on particle melting in the plasma. © 2002 Elsevier Science Ltd. All rights reserved.